IMPLEMENTASI PROGRAM JKN DALAM PENCAPAIAN UHC DI INDONESIA (SYISTEMATIC LITERATUR RIVIEW) - Agil Maritho Lauchan; Elvina, Riri Anggraini, Fitriani Pramita Gurning (CV. Adiba Aisha Amira, 2024)
The implementation of Universal Health Coverage (UHC) has been agreed to be implemented by many countries, however, achieving UHC is not always realized quickly in some countries. The JKN (National Health Insurance) program is an Indonesian government program aimed at The JKN (National Health Insurance) program is an Indonesian government program that aims to provide health protection to all Indonesian residents. The program is managed by the Health Social Security Agency (BPJS Kesehatan) and is one of the eflorts to achieve Universal Health Coverage (UHC) in Indonesia. The JKN program aims to provide public access to health services and provide financial protection. The JKN program in Indonesia can be considered as a concrete step in supporting the achievement of Universal Health Coverage by providing access to health, financial protection, and improving the quality of health services for the entire population. Based on the background of this paper, the purpose of this study is to implement the JKN program in achieving UHC in Indonesia and what are the things that support the JKN program in achieving UHC. The method applied in this study is the Literature Study method. This research involved analyzing research findings related to the topic under study. Data sources for the literature review were selected from recent journals published between 2019 and 2023. The researcher conducted a search through a search site using the Google Scholar publication database, successfully identifying 7 relevant national research journals to serve as references in this study.